Estudo químico do fungo endofítico isolado de Hortia superba (Rutaceae) na produção de compostos secundários - Formoso, Dianne Dominguez (2018)
The order Sapindales, compost for the families Rutaceae, Meliaceae, Burseraceae, Simaroubaceae, Bierbersteiniaceae, Kirkiaceae, Anacardiaceae, Sapindaceae and Nitrariaceae, is rich in various classes of speciais metabolites, being the most frequents: coumarins, alkaloids, flavonoids, quassinoides and limonoides. The family Rutaceae is characterized by a great diversity of those metabolites not common in other families the order (Silva et al., 1988) and is constituted by different genera, of which stands out Hortia, compost for five species distributed from Panama to the state of São Paulo, and some of the area Amazônica (Groppo and Pirani 2012), besides of to be endemic in the area of Minas Gerais, where take the plant as a sample. In this work the endophytic fungus belonging to the family Xylaria, was isolated .This fungus was inoculated in the malt extract agar culture medium, where was produced several secondary metabolites, and between they were separated and identified three compounds: Declorogriseofulvin, Griseofulvina, 3,4-Dihydro-8- hydroxy-3- methylisocouarin-5-carboxylic acid, Spiro[benzofuran-2(3H),1'-[2] cyclohexene]-3,4'- dione, 5-cloro-7-declorogriseofulvina, a compound that is still unpublished and 5- clorogriseofulvin. The second compound is isomer of this last substance and was identified by the NMR and Massa Spectrometry techniques. The hemolytic activity in blood was measured for the substances, resulting the griseofulvin being less toxic in blood than your analogue, as declorogriseofulvin. In addition, the biological activity of the compounds was analyzed against to the strain Staphylococcus aureus, by the Inhibitory Concentration Method for bacteria (MICs) (Barbosa. S et al, 2016), concluding as result that the substances do not have antimicrobial activity against the Gram- positive bacteria.